A Tyrannous Eye : Eudora Welty's Nonfiction and Photography - McHaney, Pearl Amelia (Book collections on Project MUSE., 2014)
"A Tyrannous Eye: Eudora Welty's Nonfiction and Photographs is the first book-length study of Eudora Welty's full range of achievements in nonfiction and photography. A preeminent Welty scholar, Pearl Amelia McHaney offers clear-eyed and complex assessments of Welty's journalism, book reviews, letters, essays, autobiography, and photographs. Each chapter focuses on one genre, filling in gaps left by previous books. With keen skills of observation, finely tuned senses, intellect, wit, awareness of audience, and modesty, Welty applied her genius in all that she did, holding a tough line on truth, breaking through "the veil of indifference to each other's presence, each other's wonder, each other's plight."McHaney's study brings critical attention to the under-evaluated genres of Welty's work and discusses the purposeful use of arguments, examples, and styles, demonstrating that Welty pursued her craft to a high standard across genres with a greater awareness of context than she admitted in her numerous interviews. Welty consistently dared new styles, new audiences, and new publishing venues in order to express her ideas to their fullest, always with readers in mind. It is "serious daring," as she wrote in One Writer's Beginnings, that makes for great writing. In "Place in Fiction," Welty asks, "How can you go out on a limb if you do not know your own tree? No art ever came out of not risking your neck. And risk--experiment--is a considerable part of the joy of doing.""--